The Influence Of Work Motivation And Work Facilities On Employee Performance At CV.Tunas Barkah Mebeul Company - Mubarok, Dede Lutfi; Fitriadi, Budhi Wahyu; Rahwana, Kusuma Agdhi (Universitas Dehasen Bengkulu, 2023)
This study aims to identify and analyze the effect of work motivation and work facilities on employee performance at CV. Tunas Barkah Mebeul. The method used in this study is causality through a census approach. With a research sample of 40 employees of CV. Tunas Barkah Mebeul Company. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Work Motivation has a very good rating classification, Work Facilities have a very good rating classification while Employee Performance has a good classification for Employees of the Company CV. Tunas Barkah Mebeul. Taken together, Work Motivation and Work Facilities have a significant influence on Employee Performance at CV. Tunas Barkah Mebeul Company Employees. Partially, work motivation has significant effect on employee performance at CV. Tunas Barkah Mebeul company employees. Partially, Work Facilities have a significant effect on Employee Performance at CV. Tunas Barkah Mebeul Company Employees